DAYA SAING KOMODITI HORTIKULTURA INDONESIA DI PASAR ASEAN - Yuanita Chandra Gunawan; Firman Rosjadi Djoemadi; Sugeng Hariadi (CALYPTRA, 2018)
Horticulture is one of Indonesia's agricultural sub-sectors with quite good economic potential that can create income, business opportunities, employment opportunities, as well as upstream-downstream linkages and with other sectors, and also has a good export potential in the international market, such as ASEAN market. This research is to analyze the condition and position of competitiveness of Indonesian horticulture commodity in ASEAN market in 2012-2016, and to formulate strategies that can support the increasing value and competitiveness of Indonesian horticultural exports. Research on the competitiveness of Indonesian horticultural exports 2012-2016 was analyzed using Revealed Comparative Advantages, Export Competitiveness Index, and Acceleration Ratio. The commodities studied in this research are cut flower, mango, mangosteen, guava, avocado, watermelon, potato, tomato, and temulawak which is the leading commodity of Indonesia in 2012. Based on the results of the three analyzes, it can be concluded that there are horticultural commodities has a high export competitiveness in the ASEAN market because it meets all three criteria specified, but of course there are horticultural commodities which still have low export competitiveness in the ASEAN market. It is necessary to create strategy in order to increase the value and also improve the quality of products and the competitiveness of Indonesian horticulture in the ASEAN market.